Multiple Streams Framework (MSF) Analysis on the Adoption of the Personal Data Protection Bill - Reine Taqiyya Prihandoko; Andreo Wahyudi Atmoko (Univiversitas Dr. Djar Wattiheluw, 2025)
This research examines the adoption of Indonesia’s Personal Data Protection (PDP) Bill using the Multiple Streams Framework (MSF), with particular attention to how the 2022 Bjorka data breach catalyzed the convergence of the problem, policy, and political streams. Although this incident created a policy window, the subsequent stream coupling was largely reactive and premature, shaped more by symbolic political urgency than by institutional or policy readiness. The analysis demonstrates that the bill’s enactment proceeded without adequate groundwork for implementation, as evidenced by delayed regulatory development and unresolved issues concerning the establishment of an independent data protection authority. The study contributes to understanding digital governance reform in transitional political contexts, highlighting the pitfalls of crisis- driven convergence and symbolic legislative adoption. It underscores the critical need for institutional coherence, context-sensitive policy adaptation, and forward-looking governance in achieving substantive and sustainable digital policy outcomes.